The Churchills in love and war - Lovell, Mary S. (W.W. Norton, 2011)
The First Duke of Marlborough (1650-1722) was a soldier of such genius that a lavish palace, Blenheim, was built to honor his triumphs. Succeeding generations of Churchills sometimes achieved distinction but also included profligates and womanisers and were saddled with the ruinous upkeep of Blenheim. The Churchills were an extraordinary family: ambitious, impecunious, impulsive, brave, and arrogant. Winston Churchill recently voted the Greatest Briton dominates them all. His failures and his triumphs are revealed here in the context of his poignant and sometimes tragic private life